Final answer:
To solve the equation S = 5Lw + 5wh + 6hL for h, rearrange the terms to isolate h, factor h out, and then divide by the remaining coefficient to find that h = (S - 5Lw) / (5w + 6L).
Step-by-step explanation:
For solving the equation S = 5Lw + 5wh + 6hL for the variable h. To do this, we first need to bring all terms involving h to one side of the equation:
S - 5Lw = 5wh + 6hL
We can then factor out h on the right-hand side:
S - 5Lw = h(5w + 6L)
Finally, to solve for h, we divide both sides of the equation by 5w + 6L:
h = (S - 5Lw) / (5w + 6L)
The solution for h in the equation is therefore h = (S - 5Lw) / (5w + 6L).